Palestinian private sector forum - Palestinian Businessmen Association. Center for Private Sector Development (Nablus Center for Private Sector Development, 2003)
Palestinian private sector forum is meant to be an advocacy platform on issues relating to the private sector and Palestinian economy
Keywords: Business enterprises; BUSINESS ENTERPRISES; PRIVATE ENTERPRISES; PRIVATE SECTOR; PERIODICALS; PALESTINE